Bimetal monatomic modified flaky porous carbon material derived from silk fabric as well as preparation method and application of flaky porous carbon material

By modifying the flaky porous carbon material with bimetallic single atoms derived from silk fabric, the problems of electronic insulation and volume change of lithium-sulfur battery positive electrode materials were solved, and high-load and long-life lithium-sulfur battery positive electrode materials were achieved, which simplified the preparation process and reduced costs.

CN120600808APending Publication Date: 2025-09-05SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410240855.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-04
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

Existing lithium-sulfur battery positive electrode materials have problems such as electronic insulation, volume change and easy dissolution of lithium polysulfide, which have hindered the commercialization process. In addition, the synthesis of traditional two-dimensional porous carbon materials is complex and costly.

Method used

The flaky porous carbon material modified with bimetallic single atoms derived from silk fabric is prepared by high-temperature heat treatment and acid washing, and combined with metal molten salt as a template and dopant to form a heterogeneous single-atom structure, thereby improving the catalytic activity and stability.

Benefits of technology

It has achieved high-load, long-life lithium-sulfur battery positive electrode materials, improved specific capacity and rate performance, simplified the preparation process and reduced costs, and is suitable for commercial high-performance lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120600808A_ABST
    Figure CN120600808A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy, and particularly relates to a bimetallic monatomic modified flaky porous carbon material derived from silk fabric as well as a preparation method and application of the bimetallic monatomic modified flaky porous carbon material. In order to overcome the defects of poor electrochemical performance, complex synthesis process and the like of a lithium-sulfur battery positive electrode material in the prior art, the invention provides a silk fabric derived bimetallic monatomic modified sheet porous carbon material which comprises a porous carbon material and bimetallic monatomic modified in the porous carbon material, the bimetallic single atoms are selected from two of iron, cobalt, nickel, copper, yttrium, niobium and molybdenum. The bimetallic monatomic modified sheet-shaped porous carbon material obtained by the invention has abundant two-dimensional interlayer volume, and is beneficial to improving the sulfur loading capacity and reducing the electrolyte dosage; the graphitized structure has a firm framework and is beneficial to improvement of conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy technology, and relates to a sheet-like porous carbon material modified with bimetallic single atoms derived from silk fabric, and a preparation method and application thereof, and in particular to a preparation method of a sheet-like porous carbon material modified with bimetallic single atoms derived from waste silk fabric, and its application in the positive electrode of a lithium-sulfur battery. Background Art

[0002] Sulfur exists mainly in the form of S8 at room temperature. It is abundant on earth, cheap and environmentally friendly. Its potential application as a positive electrode active material for lithium-sulfur batteries has attracted widespread attention. -1 ) and overall energy density (2600Wh kg -1 ) far exceeds that of traditional lithium-ion batteries, making lithium-sulfur batteries a major research hotspot in next-generation energy storage systems. However, shortcomings such as the electronic insulation of the active sulfur and its discharge products (Li2S2 / Li2S), the volume change of sulfur particles, and the solubility of the discharge intermediate lithium polysulfide have seriously hindered the commercialization of lithium-sulfur batteries.

[0003] To date, the most effective solution to these problems has been to employ porous carbon-based materials with specialized microstructures as conductive networks and hosts for the active sulfur in the cathode. In recent years, heterogeneous frameworks composed of porous carbon materials and active sites with synergistic adsorption and catalytic effects have been demonstrated to be optimal hosts for sulfur cathodes. Two-dimensional porous carbon, with its large surface area, excellent conductivity, and easily tunable active sites, can effectively load sulfur, slowing the volume expansion of the sulfur electrode and accelerating electron and ion transport. Furthermore, its two-dimensional structure increases the contact area between polysulfides and active sites.

[0004] However, most traditional two-dimensional porous carbon materials are prepared by template methods. The synthesis process usually requires the use of toxic template agents, and the synthesis raw materials are expensive and the process is complex. These shortcomings greatly limit the application of these host materials in lithium-sulfur batteries. Since biomass materials can still largely maintain their original texture and texture pores after carbonization, selecting a good precursor can reduce the difficulty of subsequent material processing. At the same time, biomass is rich in heteroatom doping, which has a "self-activation" effect during the carbonization process, and the derived carbon materials have natural active adsorption sites. On the other hand, the structure of metal single-atom catalysts is relatively simple and lacks interatomic cooperation. Moreover, it is difficult to achieve high activity for different catalytic reactions simultaneously by simply regulating the type of central metal atom, the atomic coordination structure, and the support structure. Although the patent document (application number 201910611999.6) discloses a lithium-philic-sulfur-philic co-doped two-dimensional layered graphitized porous carbon material, single atoms cannot be obtained under a nitrogen atmosphere, and the obtained metal elements are metal nanoparticles or metal oxides (the oxygen source comes from silk). Summary of the Invention

[0005] In order to overcome the shortcomings of poor electrochemical performance and complex synthesis process of lithium-sulfur battery positive electrode materials in the prior art, the present invention provides a silk fabric-derived bimetallic single-atom modified sheet-like porous carbon material and its preparation method and application.

[0006] In the first aspect, the present invention provides a silk fabric-derived bimetallic single-atom modified flaky porous carbon material, comprising: a porous carbon material, and bimetallic single atoms modified in the porous carbon material; the bimetallic single atoms are selected from two of iron, cobalt, nickel, copper, yttrium, niobium, and molybdenum.

[0007] In the present invention, a heterogeneous single-atom structure of bimetallic single atoms is used to introduce "side-by-side combat" and cooperation between atoms, thereby improving the activity and stability of the catalyst, and is expected to achieve multifunctional catalysis and asynchronous multi-time catalysis.

[0008] Preferably, the porous carbon material is formed by stacking two-dimensional carbon flakes with a single layer thickness of 2 to 5 nm, and the surface is wrinkled and porous.

[0009] Preferably, the specific surface area of ​​the porous carbon material is 1800 to 2500 m 2 g -1 , pore volume is 0.6~2.0cm 3 g -1 , the pore size is 1 to 20 nm.

[0010] Preferably, the bimetallic single atom comprises a first metal single atom and a second metal single atom; the loading amount of the first metal single atom is 0.5 to 1.0 at%, the loading amount of the second metal single atom is 0.5 to 1.0 at%; and the total loading amount of the bimetallic single atom is 1.0 to 2.0 at%.

[0011] In a second aspect, the present invention further provides a method for preparing a silk fabric-derived bimetallic single-atom modified sheet-like porous carbon material, comprising: (1) placing a silk precursor in an aqueous solution containing a template metal molten salt and a doped transition metal salt to obtain a mixed solution; (2) heating the obtained mixed solution in an oil bath, and then drying it to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions; (3) The obtained precursor mixture containing doped transition metal salt ions and template metal molten salt ions is first heat-treated at 750-950° C. in a mixed atmosphere of argon / hydrogen, and then acid-washed and vacuum-filtered to obtain the silk fabric-derived bimetallic single-atom modified flaky porous carbon material.

[0012] In the present invention, inexpensive and abundant waste biomass (for example, waste silk fabric) is used as a precursor, which is heat treated at high temperature and then acid-washed to obtain a sheet-like stacked porous carbon material. Elemental sulfur is then loaded by a melting method to obtain a positive electrode material suitable for high-load and long-life lithium-sulfur batteries.

[0013] Preferably, in step (1): the silk precursor is a waste silk fabric after degumming treatment; the degumming process is to cut the waste silk textile into small pieces, and boil and wash them in a carbonate solution at least twice to obtain the waste silk fabric after degumming treatment; Preferably, the carbonate in the carbonate solution is at least one of sodium carbonate, potassium carbonate and ammonium carbonate, and the concentration is 0.5 to 4.5 wt%.

[0014] Preferably, in step (1): the doped transition metal salt comprises a first doped transition metal salt and a second doped transition metal salt; Taking the total mass of the silk precursor, the template metal molten salt, and the doped transition metal salt as 100wt%, the mass percentage of the silk precursor is 5-25wt%, the mass percentage of the template metal molten salt is 12-32wt%; the mass percentage of the first doped transition metal salt is 28-58wt%, and the mass percentage of the second doped transition metal salt is 28-58wt%; The template metal molten salt includes at least one of magnesium nitrate, zinc nitrate, calcium nitrate, calcium chloride, zinc chloride, and magnesium chloride; the first doped transition metal salt and the second doped transition metal salt are selected from two of ferric chloride, cobalt chloride, nickel chloride, copper chloride, yttrium chloride, niobium chloride, and molybdenum chloride.

[0015] Preferably, the temperature of the heating treatment is 80-120° C., and the time is 8-14 hours; the temperature of the drying is 120-180° C., and the time is 2-4 hours.

[0016] Preferably, the heat treatment time is 1.5 to 5.5 hours; preferably, the heating rate of the heat treatment is 1 to 5 ° C min -1 ; The acid solution used in the acid washing is hydrochloric acid with a concentration of 2 to 6M.

[0017] In a third aspect, the present invention provides a method for preparing a positive electrode active material for a lithium-sulfur battery, comprising: Silk fabric-derived bimetallic single-atom-modified flaky porous carbon material and elemental sulfur powder were mixed at a mass ratio of 1:(3-9) and sealed in a quartz glass tube. The lithium-sulfur battery cathode active material is then heat-insulated at 150-165°C in an inert gas atmosphere for 8-16 hours. Preferably, the heating rate during the heat-insulation is 0.5-2.5°C / min. In the present invention, lithiophilic sites are simultaneously formed under a reducing atmosphere by nitrogen doping, the nitrogen source being derived from the silk itself. Most importantly, the present invention prevents oxidation and aggregation of metal single atoms under a reducing atmosphere, resulting in well-dispersed single atoms.

[0018] In a fourth aspect, the present invention provides a positive electrode active material for a lithium-sulfur battery prepared according to the above preparation method.

[0019] In a fifth aspect, the present invention provides a lithium-sulfur battery positive electrode, characterized in that it comprises: the above-mentioned lithium-sulfur battery positive electrode active material, a conductive carbon additive and a binder; Preferably, the conductive carbon additive is at least one of Super P, Ketjen black, carbon black and carbon nanotubes; Preferably, the binder is at least one of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid and polyacrylonitrile.

[0020] The present invention utilizes inexpensive, abundant waste biomass as a precursor, annealing at high temperature, and then acid washing to produce a stacked, porous carbon material. The flaky porous carbon serves a dual purpose: providing a two-dimensional interlayer with a hierarchical pore structure to mitigate volume expansion and improve the utilization of bimetallic single atoms. The synergistic effect between the bimetallic single atoms significantly enhances the interaction between polysulfides and active sites, accelerating the conversion reaction kinetics of long-chain polysulfides and promoting the deposition kinetics of lithium sulfide in a "relay" manner, thereby improving the specific capacity and rate performance of lithium-sulfur batteries.

[0021] In a sixth aspect, the present invention provides a lithium-sulfur battery, characterized in that it comprises: the above-mentioned lithium-sulfur battery positive electrode active material or the above-mentioned lithium-sulfur battery positive electrode.

[0022] Beneficial effects of the present invention: (1) The waste silk fabric-derived bimetallic single-atom-modified flaky porous carbon material of the present invention has a rich two-dimensional interlayer volume, which is beneficial to increasing the sulfur loading and reducing the amount of electrolyte used; the graphitized structure has a strong skeleton and is beneficial to improving the conductivity; in the structure of two different metal single-atom coupling, a strong adsorption effect on long-chain polysulfides and a promoting effect on the Li2S2 / Li2S electrodeposition kinetics can be achieved respectively, which is beneficial to promoting the conversion reaction of polysulfides and improving the specific capacity and rate performance of lithium-sulfur batteries; (2) The present invention utilizes waste silk fabric as a porous carbon precursor for the first time, and adopts metal molten salt as both a high-temperature solvent and a pore-forming agent. The metal molten salt acts as a cross-linking template during the high-temperature carbonization of heteroatom-rich silk, thereby obtaining a two-dimensional sheet-like porous carbon material. Furthermore, two different transition metal salts are added to obtain a bimetallic single-atom modified host skeleton suitable for the positive electrode of a lithium-sulfur battery. This preparation process only requires high-temperature annealing and a simple pickling process, with a short process, easy operation, low cost, and is very conducive to large-scale production. (3) After the waste silk fabric-derived bimetallic single-atom-modified flaky porous carbon material of the present invention is loaded with elemental sulfur, a composite lithium-sulfur battery positive electrode material of sulfur / bimetallic single-atom-modified flaky porous carbon material with high sulfur loading, large reversible specific capacity, stable long-cycle performance, and good rate performance is obtained, which is particularly suitable for commercial high-performance lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Transmission electron micrograph of a sheet-like porous carbon material modified with Fe / Co bimetallic single atoms derived from waste silk fabric and its corresponding element distribution map (Example 1); Figure 2 The adsorption-desorption curves of the Fe / Co bimetallic single-atom modified flaky porous carbon material derived from waste silk fabrics are shown in the inset, and the pore size distribution diagram is shown in Example 1. Figure 3 This is a scanning electron micrograph of a composite of a sheet-like porous carbon material modified with Fe / Co bimetallic single atoms derived from waste silk fabric and active sulfur (Example 2); Figure 4 Thermogravimetric analysis curve of the composite of Fe / Co bimetallic single atom-modified sheet-like porous carbon material derived from waste silk fabric and active material sulfur (Example 2); Figure 5 This is a comparison chart of the rate performance of the lithium-sulfur battery positive electrode material of Example 2; Figure 6 This is a cycle performance diagram of the high sulfur loading lithium sulfur battery positive electrode material of Example 2. DETAILED DESCRIPTION

[0024] The present invention is further described below through the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention.

[0025] In the present disclosure, the sulfur host material that can be used for the positive electrode of a lithium-sulfur battery is a sheet-like porous carbon material derived from waste silk fabric and modified with bimetallic single atoms. Specifically, the bimetallic single atoms modified on the carbon material are any two of iron, cobalt, nickel, copper, yttrium, niobium, and molybdenum. The specific surface area of ​​the porous carbon material is 1800 to 2500 m 2 g -1 , pore volume is 0.6~2.0cm 3 g -1 The carbon material is formed by stacking two-dimensional carbon sheets with a single layer thickness of 2 to 5 nm, and the surface is wrinkled and porous.

[0026] The preparation method of the waste silk fabric-derived bimetallic single-atom modified flaky porous carbon material of the present invention includes the following technical solutions.

[0027] Cut the collected waste textiles into pieces with a size of 1.5 cm 2 The silk fabric pieces are collected and washed three times by boiling in a carbonate solution of a certain concentration to obtain clean degummed silk as a porous carbon precursor. The carbonate in the carbonate solution is at least one of sodium carbonate, potassium carbonate, and ammonium carbonate, and the solution concentration is 0.5 to 4.5 wt%.

[0028] The silk precursor is transferred into 25 ml of an aqueous solution containing a template metal molten salt and a doping transition metal salt to obtain a mixed solution. The precursor mixture contains 5 to 25 wt% of silk, 12 to 32 wt% of the template metal molten salt, and 28 to 58 wt% of the two doping transition metal salts, respectively.

[0029] The mixed solution was heated in an oil bath at 80-120° C., fully stirred overnight, and then transferred to an oven at 120-180° C. for drying for 4 hours to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions.

[0030] The precursor mixture was transferred to a tube furnace and heated at 1-5 °C min-1 in an argon / hydrogen mixed atmosphere. -1 The heating rate is from room temperature to 750-950℃ and maintained for 1.5-5.5 hours.

[0031] Finally, after cooling to room temperature and washing with 2-6 M hydrochloric acid, the waste silk fabric-derived bimetallic single-atom modified sheet-like porous carbon material was obtained by vacuum filtration.

[0032] Preparation of positive electrode active material of lithium-sulfur battery: The bimetallic single atom-modified flaky porous carbon material derived from waste silk fabric and elemental sulfur powder were ground and mixed evenly at a mass ratio of 1: (3-9), and sealed in a quartz glass tube. The mixture was heated at 0.5-2.5℃ min from room temperature under an inert gas atmosphere. -1 The temperature is raised to 150-165° C., kept at this temperature for 8-16 hours, and then cooled to room temperature to obtain an active material suitable for the positive electrode of a lithium-sulfur battery.

[0033] The following is an illustrative example of the preparation process of the positive electrode of a lithium-sulfur battery.

[0034] The positive electrode active material of the lithium-sulfur battery, the conductive carbon additive, and the polyvinylidene fluoride binder are ground into a uniform viscous slurry in an N-methyl-2-pyrrolidone solution at a mass ratio of 8:1:1 or 7:2:1, and are used to prepare the positive electrode of the lithium-sulfur battery.

[0035] The present invention provides a lithium-sulfur battery, comprising: the above-mentioned positive electrode active material of the lithium-sulfur battery or the positive electrode of the lithium-sulfur battery.

[0036] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all fall within the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description herein, and are not limited to the specific numerical values ​​exemplified below.

[0037] Example 1: (1) Cut the collected waste textiles into pieces with a size of 1.5 cm 2These silk fabric pieces were collected and washed three times by boiling in a 1.5 wt% sodium carbonate solution to obtain clean degummed silk as a porous carbon precursor. (2) transferring the silk precursor into 25 ml of an aqueous solution containing 3.75 g of anhydrous zinc chloride, 5.07 g of anhydrous ferric chloride, and 4.06 g of anhydrous cobalt chloride to obtain a mixed solution; (3) heating the mixed solution in an oil bath at 100°C, stirring thoroughly overnight, keeping the mixture warm for 4 hours, and then transferring the mixture to an oven at 150°C for drying to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions; (4) Then, the precursor mixture was transferred to a tube furnace and heated at 3 °C min -1 The heating rate was from room temperature to 900 °C and maintained for 2 hours; (5) Finally, after cooling to room temperature and washing with 2 M hydrochloric acid, the waste silk fabric-derived Fe / Co bimetallic single-atom-modified sheet-like porous carbon material (DSA-SilkC) was obtained by vacuum filtration. The loading amount of Fe metal single atoms was 0.5 at%, and the loading amount of Co metal single atoms was 0.7 at%.

[0038] The transmission electron microscopy image of the DSA-SilkC flaky porous carbon material obtained in Example 1 and its corresponding element distribution are shown in FIG. Figure 1 The BET specific surface area of ​​the Fe / Co bimetallic single atom modified porous carbon material is 2220.15 m 2 g -1 , with a total pore volume of 1.12 cm 3 g -1 ,like Figure 2 shown.

[0039] Comparative Example 1: (1) Cut the collected waste textiles into pieces with a size of 1.5 cm 2 These silk fabric pieces were collected and washed three times by boiling in a 1.5 wt% sodium carbonate solution to obtain clean degummed silk as a porous carbon precursor. (2) transferring the silk precursor into 25 ml of an aqueous solution containing 3.75 g of anhydrous zinc chloride and 10.14 g of anhydrous ferric chloride to obtain a mixed solution; (3) heating the mixed solution in an oil bath at 100°C, stirring thoroughly overnight, keeping the mixture warm for 4 hours, and then transferring the mixture to an oven at 150°C for drying to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions; (4) The precursor mixture was transferred to a tube furnace and heated at 3 °C min under an argon / hydrogen mixed atmosphere.-1 The heating rate was from room temperature to 900 °C and maintained for 2 hours; (5) Finally, after cooling to room temperature and washing with 2 M hydrochloric acid, the waste silk fabric-derived Fe single atom-modified sheet-like porous carbon material (Fe-SilkC) was obtained by vacuum filtration, with a Fe single atom loading of 0.3 at%.

[0040] Comparative Example 2: (1) Cut the collected discarded textiles into pieces with a size of 1.5 cm 2 These silk fabric pieces were collected and washed three times by boiling in a 1.5 wt% sodium carbonate solution to obtain clean degummed silk as a porous carbon precursor. (2) transferring the silk precursor into 25 ml of an aqueous solution containing 3.75 g of anhydrous zinc chloride and 8.12 g of anhydrous cobalt chloride to obtain a mixed solution; (3) heating the mixed solution in an oil bath at 100°C, stirring thoroughly overnight, keeping the mixture warm for 4 hours, and then transferring the mixture to an oven at 150°C for drying to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions; (4) The precursor mixture was transferred to a tube furnace and heated at 3 °C min under an argon / hydrogen mixed atmosphere. -1 The heating rate was from room temperature to 900 °C and maintained for 2 hours; (5) Finally, after cooling to room temperature and washing with 2 M hydrochloric acid, the waste silk fabric-derived Co single-atom-modified sheet-like porous carbon material (Co-SilkC) was obtained by vacuum filtration, with a Co metal single-atom loading of 1.2 at%.

[0041] Example 2: The DSA-SilkC of Example 1 or the Fe-SilkC of Comparative Example 1, the Co-SilkC of Comparative Example 2 and the elemental sulfur powder were ground and mixed at a mass ratio of 1:4, and sealed in a quartz glass tube. -1 The temperature was raised to 155°C, kept for 12 hours, and then cooled to room temperature to obtain lithium-sulfur battery cathode composite materials DSA-SilkC / S or Fe-SilkC / S, Co-SilkC / S. After being compounded with elemental sulfur, DSA-SilkC / S still maintained a two-dimensional flaky porous carbon morphology and no large pieces of elemental sulfur agglomerate. Figure 3 The actual sulfur content was measured by thermogravimetric analysis to be 83.9% by mass, as shown in Figure 4 shown.

[0042] The lithium-sulfur battery positive electrode composite material obtained in Example 2, conductive carbon, and polyvinylidene fluoride were dispersed in a certain volume of N-methyl-2-pyrrolidone at a mass ratio of 8:1:1 and mixed evenly to form a slurry. The slurry was then coated on a carbon paper current collector with a scalpel and vacuum-dried at 50°C overnight to obtain a positive electrode sheet suitable for lithium-sulfur batteries. The sulfur loading of each positive electrode sheet was 1.5 mg cm -2 . Then, the metal lithium sheet was used as the counter electrode, the electrolyte was a mixed solution of 1M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) as the lithium salt, ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL) with a volume ratio of 1:1 as a mixed solvent, 0.2M LiNO3 as an additive, Celgard 3501 as a separator, and CR2025 button cells were assembled in an argon atmosphere glove box. The moisture and oxygen contents in the glove box were both less than 1ppm. The charge and discharge cycle test of the lithium-sulfur battery was carried out on a blue battery test instrument. The rate performance of the lithium-sulfur battery was evaluated at different rates from 0.2 to 10C. The DSA-SilkC / S electrode provided 1311.2mAh g at 0.2C, 0.5C, 1C, 2C, 5C and 10C, respectively. -1 、1048.7mAh g -1 , 972.6mAh g -1 、893.4mAh g -1 , 780.4mAh g -1 and 538.6mAh g -1 High specific capacity ( Figure 5 When restored to 0.2C, 1038.4mAh g is still available. -1 The high reversible capacity proves that DSA-SilkC / S still has excellent cycle reversibility even after high-speed charge / discharge processes. However, under the same test conditions, the electrochemical performance of the lithium-sulfur battery positive electrode composite materials Fe-SilkC / S and Co-SilkC / S obtained from Fe-SilkC and Co-SilkC in Comparative Examples 1 and 2 were lower than that of DSA-SilkC / S. Furthermore, when the sulfur loading of DSA-SilkC / S as a lithium-sulfur battery positive electrode material was increased to 8.5 mg cm -2 , when the electrolyte volume is 8μl per mg of sulfur, it still shows excellent electrochemical performance, such as Figure 6 At 0.3 mA cm -2 The areal capacity at this current density is 8.6 mAh cm -2 Even at a high current density of 1.0 mA cm -2 Its surface capacity can also be stabilized at 4.8 mAh cm -2 To 120 laps.

[0043] Example 3: Cut the collected waste textiles into pieces with a size of 1.5 cm 2 Small pieces of silk fabric were collected and washed three times by boiling in a 2.0 wt% potassium carbonate solution to obtain clean degummed silk as a porous carbon precursor. The silk precursor was transferred into 25 ml of an aqueous solution containing 2.75 g of anhydrous zinc chloride, 4.20 g of anhydrous copper chloride, and 4.05 g of anhydrous nickel chloride to obtain a mixed solution; The mixed solution was heated in an oil bath at 120°C, stirred thoroughly overnight, kept warm for 4 hours, and then transferred to an oven at 180°C for drying to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions; Then, the precursor mixture was transferred to a tube furnace and heated at 5 °C min -1 The heating rate was from room temperature to 850 °C and maintained for 5 hours; Finally, after cooling to room temperature and washing with 4M hydrochloric acid, the waste silk fabric-derived Cu / Ni bimetallic single-atom-modified sheet-like porous carbon material was obtained by vacuum filtration. The loading of Cu metal single atoms was 0.8at%, and the loading of Ni metal single atoms was 0.6at%.

[0044] Example 4: Cut the collected waste textiles into pieces with a size of 1.5 cm 2 Small pieces of silk fabric were collected and washed three times by boiling in a 3.5 wt% ammonium carbonate solution to obtain clean degummed silk as a porous carbon precursor. The silk precursor was transferred into 25 ml of an aqueous solution containing 2.62 g of anhydrous magnesium chloride, 5.07 g of anhydrous ferric chloride, and 6.10 g of anhydrous yttrium chloride to obtain a mixed solution; The mixed solution was heated in an oil bath at 150°C, stirred thoroughly overnight, kept warm for 4 hours, and then transferred to an oven at 180°C for drying to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions; Then, the precursor mixture was transferred to a tube furnace and heated at 5 °C min -1 The heating rate was from room temperature to 950 °C and maintained for 1 hour; Finally, after cooling to room temperature and washing with 6M hydrochloric acid, the waste silk fabric-derived Fe / Y bimetallic single-atom-modified sheet-like porous carbon material was obtained by vacuum filtration. The loading of Fe metal single atoms was 0.9at% and that of Y metal single atoms was 0.6at%.

[0045] Example 5: Cut the collected waste textiles into pieces with a size of 1.5 cm 2 Small pieces of silk fabric were collected and washed three times by boiling in a 4.5 wt% ammonium carbonate solution to obtain clean degummed silk as a porous carbon precursor. The silk precursor was transferred into 25 ml of an aqueous solution containing 3.05 g of anhydrous calcium chloride, 4.06 g of anhydrous cobalt chloride, and 8.44 g of anhydrous niobium chloride to obtain a mixed solution; The mixed solution was heated in an oil bath at 100°C, stirred thoroughly overnight, kept warm for 4 hours, and then transferred to an oven at 150°C for drying to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions; Then, the precursor mixture was transferred to a tube furnace and heated at 2 °C min -1 The heating rate was from room temperature to 900 °C and maintained for 2 hours; Finally, after cooling to room temperature and washing with 5M hydrochloric acid, the waste silk fabric-derived Co / Nb bimetallic single-atom-modified sheet-like porous carbon material was obtained by vacuum filtration. The loading of Co metal single atoms was 0.7at% and that of Nb metal single atoms was 0.5at%.

[0046] Example 6: Cut the collected waste textiles into pieces with a size of 1.5 cm 2 Small pieces of silk fabric were collected and washed three times by boiling in a 0.5 wt% ammonium carbonate solution to obtain clean degummed silk as a porous carbon precursor. The silk precursor was transferred into 25 ml of an aqueous solution containing 3.75 g of anhydrous zinc chloride, 4.05 g of anhydrous nickel chloride, and 8.54 g of anhydrous molybdenum chloride to obtain a mixed solution; The mixed solution was heated in an oil bath at 80°C, stirred thoroughly overnight, kept warm for 4 hours, and then transferred to an oven at 120°C for drying to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions; Then, the precursor mixture was transferred to a tube furnace and heated at 1 °C min -1 The heating rate was from room temperature to 800 °C and maintained for 5 hours; Finally, after cooling to room temperature and washing with 2M hydrochloric acid, the waste silk fabric-derived Ni / Mo bimetallic single-atom-modified sheet-like porous carbon material was obtained by vacuum filtration. The loading of Ni metal single atoms was 0.7 at%, and the loading of Mo metal single atoms was 1.0 at%.

[0047] Finally, it is necessary to explain here that the above embodiments are only used to further illustrate the technical solution of the present invention in detail and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above content of the present invention all fall within the scope of protection of the present invention.

Claims

1. A silk fabric-derived bimetallic single-atom modified sheet-like porous carbon material, characterized in that: include: Porous carbon material, and bimetallic single atoms modified in the porous carbon material; the bimetallic single atoms are selected from two of iron, cobalt, nickel, copper, yttrium, niobium, and molybdenum.

2. The silk fabric-derived bimetallic single-atom modified sheet-like porous carbon material according to claim 1, characterized in that: The porous carbon material is formed by stacking two-dimensional carbon flakes with a single layer thickness of 2 to 5 nm, and the surface is wrinkled and porous.

3. The silk fabric-derived bimetallic single-atom modified sheet-like porous carbon material according to claim 1 or 2, characterized in that: The specific surface area of ​​the porous carbon material is 1800 to 2500 m 2 g -1 , pore volume is 0.6~2.0cm 3 g -1 , the pore size is 1 to 20 nm.

4. The silk fabric-derived bimetallic single-atom modified sheet-like porous carbon material according to any one of claims 1 to 3, characterized in that: The bimetallic single atom comprises a first metal single atom and a second metal single atom; the loading amount of the first metal single atom is 0.5 to 1.0 at%, and the loading amount of the second metal single atom is 0.5 to 1.0 at%; The total loading amount of the bimetallic single atoms is 1.0 to 2.0 at%; Preferably, the silk fabric-derived bimetallic single-atom modified flaky porous carbon material is doped with nitrogen and oxygen.

5. A method for preparing a silk fabric-derived bimetallic single-atom modified sheet-like porous carbon material according to any one of claims 1 to 4, characterized in that: include: (1) placing a silk precursor in an aqueous solution containing a template metal molten salt and a doped transition metal salt to obtain a mixed solution; (2) heating the obtained mixed solution in an oil bath, and then drying it to obtain a precursor mixture containing doped transition metal salt ions and template metal molten salt ions; (3) The obtained precursor mixture containing doped transition metal salt ions and template metal molten salt ions is first heat-treated at 750-950° C. in a mixed atmosphere of argon / hydrogen, and then acid-washed and vacuum-filtered to obtain the silk fabric-derived bimetallic single-atom modified flaky porous carbon material.

6. The preparation method according to claim 5, characterized in that In step (1), the silk precursor is a waste silk fabric after degumming treatment; the degumming process comprises cutting the waste silk textile into small pieces, and boiling and washing them in a carbonate solution at least twice to obtain the waste silk fabric after degumming treatment; Preferably, the carbonate in the carbonate solution is at least one of sodium carbonate, potassium carbonate and ammonium carbonate, and the concentration is 0.5 to 4.5 wt%.

7. The preparation method according to claim 5, characterized in that In step (1): the doped transition metal salt comprises a first doped transition metal salt and a second doped transition metal salt; Taking the total mass of the silk precursor, the template metal molten salt, and the doped transition metal salt as 100wt%, the mass percentage of the silk precursor is 5-25wt%, the mass percentage of the template metal molten salt is 12-32wt%; the mass percentage of the first doped transition metal salt is 28-58wt%, and the mass percentage of the second doped transition metal salt is 28-58wt%; The template metal molten salt includes at least one of magnesium nitrate, zinc nitrate, calcium nitrate, calcium chloride, zinc chloride, and magnesium chloride; The first doped transition metal salt and the second doped transition metal salt are selected from two of ferric chloride, cobalt chloride, nickel chloride, copper chloride, yttrium chloride, niobium chloride, and molybdenum chloride.

8. The preparation method according to claim 5, characterized in that The heating temperature is 80-120°C for 8-14 hours; the drying temperature is 120-180°C for 2-4 hours; The heat treatment time is 1.5 to 5.5 hours; preferably, the heating rate of the heat treatment is 1 to 5 ° C min -1 ; The acid solution used in the acid washing is hydrochloric acid with a concentration of 2 to 6M.

9. A method for preparing a positive electrode active material for a lithium-sulfur battery, characterized in that: include: The silk fabric-derived bimetallic single-atom modified flaky porous carbon material according to any one of claims 1 to 4 and elemental sulfur powder are mixed in a mass ratio of 1:(3-9) and sealed in a quartz glass tube; Then, heat preservation is carried out at 150-165° C. in an inert gas atmosphere for 8-16 hours to obtain the lithium-sulfur battery positive electrode active material; Preferably, the heating rate of the thermal insulation is 0.5-2.5°C / min.

10. A positive electrode active material for a lithium-sulfur battery prepared according to the preparation method according to claim 10.

11. A lithium-sulfur battery positive electrode, characterized in that: Comprising: the lithium-sulfur battery positive electrode active material according to claim 11, a conductive carbon additive and a binder; Preferably, the conductive carbon additive is at least one of Super P, Ketjen black, carbon black and carbon nanotubes; Preferably, the binder is at least one of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid and polyacrylonitrile.

12. A lithium-sulfur battery, characterized in that: include: The lithium-sulfur battery positive electrode active material according to claim 10 or the lithium-sulfur battery positive electrode according to claim 11.

Citation Information

Patent Citations

  • A two-dimensional layered graphitized porous carbon material co-doped with lithium- and sulfide sites, its preparation method and application

    CN112201785B